Hubungan Antara Minat, Motivasi Belajar dan Pengetahuan Literasi Siswa Terhadap Hasil Belajar di Sekolah Menengah Kejuruan (SMK) - Srijadi Gowa; M. Ichsan Ali; Hasanah Nur (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to discover the description of students’ learning interest, learning motivation, knowledge of literacy, and learning outcomes at SMKN 1 Takalar and the relationship of learning interest, learning motivation, and knowledge of literacy on learning outcomes in Basic Programming Subject. The research method employed ex-post facto research. The total population was 120 people and the sample size was 89 students obtained by using proportional random sampling technique. Data collection was conducted by employing documentation and questionnaires. The prerequisite test employed the normality test, linearity test, and multicollinearity test. Hypothesis testing employed simple linear regression and multiple linear regression. The results of the study reveal that: (1) the students’ learning interest is in very high category, (2) the students’ learning motivation is in very high category, (3) the students' literacy knowledge is in high category, (4) the learning outcomes in Basic Programming are in good category, (5) there is a relationship between the students’ learning interest and learning outcomes in Basic Programming Subject of the TKJ Department at SMKN 1 Takalar. The test indicates the sig. value is 0.010 < 0.05 with a contribution of 7.3%, (6) there is a relationship between the students’ learning motivation and learning outcomes in Basic Programming Subject of the TKJ Department at SMKN 1 Takalar. The test indicates the sig. value is 0.000 < 0.05 with a contribution of 19.8%, (7) there is a relationship between the students’ literacy knowledge and learning outcomes in Basic Programming Subject of the TKJ Department at SMKN 1 Takalar. The test indicates the sig. value is 0.033 < 0.05 with a contribution of 5.1%, and (8) there is a relationship between learning interest, learning motivation, and knowledge of literacy on learning outcomes in Basic Programming Subject of the TKJ Department at SMKN 1 Takalar. The result shows the sig. value is 0.000 < 0.05 with a contribution of 30.3%. Therefore, this research hypothesis is accepted. Keywords: learning interests, learning motivation, literacy knowledge, learning outcomes, basic programming